2016
DOI: 10.1080/10401334.2016.1155460
|View full text |Cite
|
Sign up to set email alerts
|

Does Research Training During Residency Promote Scholarship and Influence Career Choice? A Cross-Sectional Analysis of a 10-Year Cohort of the UCSF–PRIME Internal Medicine Residency Program

Abstract: Our results support the concept that providing residents with an individualized learning pathway focusing on clinical outcomes research during residency enables them to successfully publish manuscripts and access mentorship, and may influence subsequent career choice. Implementation of individualized residency program tracks that nurture academic interests along with clinical skills can support career development within medicine residency programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…More frequent reports indicate that 25–35% of residents published or present papers during training [2,4]. Recent data regarding a large national survey of 252 internal medicine residency programs indicated that overall 36% of residents presented abstracts and 12% published manuscripts and 3% published book chapters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More frequent reports indicate that 25–35% of residents published or present papers during training [2,4]. Recent data regarding a large national survey of 252 internal medicine residency programs indicated that overall 36% of residents presented abstracts and 12% published manuscripts and 3% published book chapters.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, this was the main reason programs were cited for deficiencies. Numerous articles have been published regarding complex and costly methods to enhance scholarship [27]. The intent of the current paper is to discuss methods employed in a small, community-based internal medicine residency and to compare the results with recently published data.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the pathways that have been explored include appointing a dedicated director to facilitate resident research, 3 creating a comprehensive three-year research curriculum, 4 and developing a research-focused residency track. 5 Other specialties have created Resident Research Days, 6 structured research curricula, [7][8][9] and promoted a point-based reward system. 10 Such programs have resulted in increased scholarship by residents.…”
Section: Introductionmentioning
confidence: 99%
“…10 Such programs have resulted in increased scholarship by residents. 4,5,[7][8][9] For example, one research curriculum implemented in a general surgery program incorporated structured mentoring with annual milestones. Resident publications increased by 720%.…”
Section: Introductionmentioning
confidence: 99%
“…4 Residents provided training in research are more likely to continue with scholarly pursuits after graduation. 6 However, scholarship incorporates more than research. A residency program can embrace the expanded definition of scholarship to enhance its outcome.…”
Section: Meeting Scholarly Activity Requirements In a Family Medicinementioning
confidence: 99%